The Clinical Engineering–Information Technology Professional Practice Interface: The Core Professional Task of Clinical Informatics and Its Relation to Clinical Engineering. Issue 3 (July 2021) - Chartash, David; Grout, Randall W.
Abstract : Clarifying the professional roles between clinical engineers and clinical informaticists potentially will reconcile the clinical engineering and information technology divide, yet the applied science of informatics lacks a defined core task relative to engineering design. Presenting a case study about the design and deployment of a clinical decision support system, we define a core task of informatics. Analyzing this case study given the complexity of clinical systems, we conclude that informatics seeks to solve problems at a hierarchical level above clinical engineering. Attention to the systems complexity of solutions to clinical problems is therefore necessary to demarcate roles and responsibilities between the professions.